2012
DOI: 10.4103/0377-4929.97853
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous amyloidosis: A clinico-pathological study with emphasis on polarized microscopy

Abstract: Of the 45 cases of clinically suspected amyloidosis, 32 cases were proven histopathologically as primary cutaneous amyloidosis and confirmed by congo red stain under polarized light which showed apple green birefringence. Among the two types of PCA, lichen amyloidosis was the most common variant accounting to 65.63% with pure cases of macular amyloidosis accounting for only 15.63%. Biphasic amyloidosis was seen in 18.75%. Knee was the commonest site of involvement with pruritis being the most common symptom. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 1 publication
4
26
0
6
Order By: Relevance
“…11 On the other hand, a study from South India found lichen amyloidosis to be the more common variant in their study of primary cutaneous amyloidosis. 12 A female preponderance was noted in our study similar to previous studies on cutaneous amyloidosis. 9,10,11 It has been proposed that trauma to the skin due to long standing pruritus leads to scratching, keratinocyte degradation and ultimately laying down of amyloid.…”
Section: Discussionsupporting
confidence: 79%
“…11 On the other hand, a study from South India found lichen amyloidosis to be the more common variant in their study of primary cutaneous amyloidosis. 12 A female preponderance was noted in our study similar to previous studies on cutaneous amyloidosis. 9,10,11 It has been proposed that trauma to the skin due to long standing pruritus leads to scratching, keratinocyte degradation and ultimately laying down of amyloid.…”
Section: Discussionsupporting
confidence: 79%
“…The histopathological compatibility was 92.3% in our study whereas other studies show 71%. 12 The sensitivity of congo-red staining in detection of amyloid was 53% in our study. However the study by Vijaya et al showed 100% sensitivity.…”
mentioning
confidence: 80%
“…These findings were consistent with the findings of Vijaya et al where LA was the more common variant at 61.54%. 12 Amyloid can be suspected on routine hematoxylin and eosin stain, and has to be confirmed by visualising congored stained slides under polarised light for apple-green birefringence. Eosinophilic deposits can also be due to hyalinised collagen.…”
mentioning
confidence: 99%
“…Manoma, kad nugaros trynimas, braižymas kempinėmis, rankšluos-čiais ar šepečiais turi įtakos keratinocitų apoptozei, todėl ši PLOA forma dar vadinama trinties ar rankšluosčio amiloidoze [11]. Makulinė PLOA diferencijuotina nuo použde-giminės kaklo hiperpigmentacijos ("dirty neck") atopinio dermatito metu [2], melanozės, neurodermatito ir regresuojančios plokščiosios kerpligės [12]. Ji taip pat gali būti susijusi su progresuojančia sistemine skleroze, sistemine raudonąja vilklige, pachyonychia, pirmine biliarine ciroze bei kitomis ligomis [4,5].…”
unclassified